Strategi Penataan Ruang pada Kawasan Eduwisata Kuliner Tradisional Tulungagung Berbasis Arsitektur Tropis Kontemporer dalam Mendukung Kegiatan Edukatif dan Rekreatif - Erna Putri Diana; Ryski Dwi Pratowo; Fajar Hendro Utomo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Tulungagung Regency has the potential for culinary tourism that can be developed, one of which is traditional culinary. Although the Tulungagung Regency Government has presented a "Halal Culinary Area" and a "Pinka Culinary Tourism Area", the area has not fully provided an interesting visual and functional experience. Therefore, it is necessary to design a space that facilitates traditional culinary MSMEs as well as an educational and recreational place. This design carries the theme of contemporary tropical architecture by considering local climatic conditions, through the application of wide openings, cross ventilation, wide trellises, and the use of natural materials, as well as expressive styles with the shape of a rooster roof and the basic shape of an elliptical building as a symbol of adaptation to climate change and the economy in the business environment. The facilities in this design include traditional restaurants, educational bales, wiyata offices, prayer rooms, playgrounds and other supporting facilities that can attract the interest of the community and introduce traditional Tulungagung culinary.